Effect of certain phytochemicals on Aeromonas hydrophila - Kothari, Vijay; Naraniwal, Madhu; Gupta, Ankit (Research in Biotechnology, 2011)
This study was aimed at investigating effect of different phytochemicals on growth of Aermonas hydrophila. Susceptibility of A. hydrophila to seven different phytocompounds was evaluated by broth dilution assay. Among all the test compounds curcumin with a minimum inhibitory concentration of ~175 ÃŽÂ¼g/ml was found to be most effective against A. hydrophila, followed by tannic acid. Gallic acid failed to show any effect on growth of the test organism. A growth curve study in absence and presence of curcumin was also made. Since A. hydrophila is viewed as a challenging and notorious food-borne pathogen, and difficult to control owing to its resistance to many antibiotics, it is required to find novel approaches to control it. Our study found curcumin to be effective against this organism as a bacteriostatic agent at microgram concentrations.